Budaya Wanita di Indonesia: Suatu Penelusuran ke Arah Rekonstruksi - Sri Ana Handayani; Dewi Salindri (Historia, 2021)
Indonesian women culture and manner change in chronological order could be searched from written source. This research problem questioned on how the Indonesian woman culture and manner changed in old order, new order, and reformation era. As a history study, this research used historical method with four stages of work, those are heuristic, critic, interpretation, and historiography. The occasion was analysed by cultural approach with postmodern theory by Derrida. The study showed that in old order, Indonesian woman started to understand feminism. However, the authority concept still covered in patrimonial hegemony authority. In new order, Indonesian women were still divided into agrarian culture and industrial culture. Dharma Wanita concept managed to adapt feminism into domestic space and public. Indonesian women in reformation era searched for an ideal women culture format as a result of globalisation and stronger gender understanding. Conclusion from this research is that in defining an ideal women, Indonesian women, on one side still crave the berdikari (berdiri di atas kaki sendiri) feminity stereotype.